2010
DOI: 10.1109/tbme.2009.2034533
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble-Size Dependence of Focused Ultrasound-Induced Blood–Brain Barrier Opening in MiceIn Vivo

Abstract: The therapeutic efficacy of neurological agents is severely limited, because large compounds do not cross the blood–brain barrier (BBB). Focused ultrasound (FUS) sonication in the presence of microbubbles has been shown to temporarily open the BBB, allowing systemically administered agents into the brain. Until now, polydispersed microbubbles (1–10 μm in diameter) were used, and, therefore, the bubble sizes better suited for inducing the opening remain unknown. Here, the FUS-induced BBB opening dependence on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
193
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(212 citation statements)
references
References 46 publications
16
193
1
2
Order By: Relevance
“…Other FUS parameters (for example, frequency, pulse length, and pulserepetition frequency), as well as MB characteristics (for example, resonant frequency, size, and shell properties) may also be correlated with BBB opening size. For example, one previous study by our group found that the BBB opening pressure threshold for the delivery of 3 kDa dextran was significantly lower with MBs of 4 to 5 mm than 1 to 2 mm in diameter, 28 which suggests that MB size may be an important factor influencing the BBB opening size. The impact of parameters other than acoustic pressure on the BBB opening size will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 91%
“…Other FUS parameters (for example, frequency, pulse length, and pulserepetition frequency), as well as MB characteristics (for example, resonant frequency, size, and shell properties) may also be correlated with BBB opening size. For example, one previous study by our group found that the BBB opening pressure threshold for the delivery of 3 kDa dextran was significantly lower with MBs of 4 to 5 mm than 1 to 2 mm in diameter, 28 which suggests that MB size may be an important factor influencing the BBB opening size. The impact of parameters other than acoustic pressure on the BBB opening size will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 91%
“…To date, a wide class of albumin-and lipid-shelled as well as polydispersed and size-isolated microbubbles have been utilized and include Optison (1), SonoVue (19), Definity (2), and customdesigned microbubbles (9,20). Recent studies have shown that larger microbubbles (4-5 and 6-8 μm) have a lower PRP threshold for BBB disruption than smaller bubbles (1-2 μm) (9, 20) when using PLs greater than 66.7 μs.…”
Section: Discussionmentioning
confidence: 99%
“…Large radial bubble expansions may induce inertial cavitation activity, which may lead to bubble collapse due to the inertia of the surrounding media and affect the vascular physiology (8). Each type and magnitude of cavitation activity results in distinct vascular bioeffects and are dictated by the ultrasonic pulse shape and sequence, the microbubble composition and distribution (9), and the in vivo environment the microbubbles circulate (8,10). Selection of the exposure parameters is critical for effective drug delivery while minimizing side effects (11).…”
mentioning
confidence: 99%
“…23,35−37 Other parameters such as microbubble size and dose can affect the extent of BBB disruption. 38,39 Numerous efforts have been made to optimize BBB disruption, but perhaps the biggest contribution has come from development of a real-time acoustic controller. 40 Acoustic emissions are monitored and used to actively control the pressure amplitude of the ultrasound leading to a consistent BBB disruption.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%